2021
DOI: 10.1016/j.xops.2021.100016
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Atrophy and Visual Outcomes in Extensive Macular Atrophy with Pseudodrusen-like Appearance

Abstract: Purpose: To report visual outcomes and rate of retinal pigment epithelium (RPE) atrophy progression in patients with extensive macular atrophy with pseudodrusen-like appearance (EMAP).Design: Retrospective, observational study.Participants: Patients with EMAP and symptom onset before 55 years of age, at least 12 months of followup using Spectralis blue-light fundus autofluorescence (BAF) and OCT and with no other ocular or systemic conditions.Methods: Best-corrected visual acuity (BCVA), BAF, and OCT images we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
(29 reference statements)
3
17
1
Order By: Relevance
“…Additionally, SCR correlates with atrophy progression rates and circularity. The latter is another useful parameter in distinguishing EMAP and DTGA from nDTGA, and its correlation with the progression rate has already been described in the literature 5 . These findings suggest that the simultaneous presence of low circularity and SCR supports the diagnosis of EMAP or DTGA.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Additionally, SCR correlates with atrophy progression rates and circularity. The latter is another useful parameter in distinguishing EMAP and DTGA from nDTGA, and its correlation with the progression rate has already been described in the literature 5 . These findings suggest that the simultaneous presence of low circularity and SCR supports the diagnosis of EMAP or DTGA.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, nDTGA does not always exhibit the Bruch-RPE splitting. Fleckenstein M. et al have already described this feature in DTGA, and recently Romano F. et al have also documented this OCT characteristic in EMAP 3 , 5 . We surmise that this phenomenon might be compatible with the presence of basal laminar deposits, which could in turn explain the grayish appearance of the atrophy on FAF images of EMAP and DTGA.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Several studies have shown a dotted or linear area of high reflectivity in the caverns [ 1 ], whereas others denied the presence of such areas [ 7 ]. Although choroidal caverns usually occur in patients with GA [ 8 , 9 , 10 ], pachychoroid spectrum disease [ 11 , 12 , 13 , 14 , 15 ], retinal pigment epithelium (RPE) atrophy diseases such as Stargardt disease [ 16 ], best vitelliform dystrophy [ 17 ] and rod–cone dystrophy [ 7 , 18 ], they are also seen in normal eyes or choroidal osteoma [ 19 ]. Although previous studies have described the shape and size of choroidal caverns, they have not systematically analyzed the related characteristics of choroidal caverns.…”
Section: Introductionmentioning
confidence: 99%